2011
DOI: 10.3109/09638288.2011.575529
|View full text |Cite
|
Sign up to set email alerts
|

Assessing disability in morbidly obese individuals: the Italian Society of Obesity test for obesity-related disabilities

Abstract: The TSD-OC is a reliable and valid instrument for measuring self-reported disability in obese subjects. It may represent an important tool for establishing rehabilitation needs in individuals with obesity-related disability, for planning appropriate rehabilitation programmes and for evaluating their effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 43 publications
1
24
1
1
Order By: Relevance
“…In the validation study, the TSD-OC measure showed an excellent stability at the test–retest ( r = 0.90) and an excellent internal consistency (Cronbach’s > 0.90). Moreover, a significant correlation was found with SF-36 scores, the distance walked at the 6 min walk test, and grip strength, and a total of 26 ICF (International Classification of Functioning, Disability and Health) categories, mostly related to the area of mobility, were correlated to TSD-OC score [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the validation study, the TSD-OC measure showed an excellent stability at the test–retest ( r = 0.90) and an excellent internal consistency (Cronbach’s > 0.90). Moreover, a significant correlation was found with SF-36 scores, the distance walked at the 6 min walk test, and grip strength, and a total of 26 ICF (International Classification of Functioning, Disability and Health) categories, mostly related to the area of mobility, were correlated to TSD-OC score [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The total score (0 to 360) represents the severity of the disability status. A TSD-OC score, higher than 33%, is consistent with a high level of obesity-related disability [17]. …”
Section: Methodsmentioning
confidence: 99%
“…Some of these instruments measure sections of the ICF classification structure, such as A&P: examples of this are the IMPACT-S, the screener part of the ICF Measure of Participation and Activities questionnaire [62], the Norwegian Function Assessment Scale (NFAS) [63]. Few instruments have been developed that specifically focus on a disease: to our knowledge, the Functional Assessment in Migraine (FAIM) questionnaire [64] and the Italian Society of Obesity test for obesity-related disabilities (TSD-OC) [65] are the only developed ICF-based disease specific disability assessment tools. We developed the MG-DIS based on different steps: a preliminary set of items was drawn based on available literature and previous experience with ICF-based instruments application in patients with MG.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study disability was assessed through the TSD-OC test, a recently validated tool specifically designed to assess disability level in obese subjects [29]. The TSD-OC test is composed of 36 items divided into seven sections (pain, stiffness, activities of daily living and indoor mobility, housework, outdoor activities, occupational activities and social life).…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid conditions were assessed using the Charlson comorbidity index score [28]. Disability was evaluated using the test for obesity-related disabilities (TSD-OC test) by the Italian Society of Obesity [29]. Quality of life was assessed by the administration of the Short-Form Health Survey questionnaire (SF-36 questionnaire) [30], and anxiety and depression were measured using the Symptom Checklist-90 (SCL-90 questionnaire) [31].…”
Section: Health Disability and Quality Of Life Assessmentmentioning
confidence: 99%